Analgesic efficacy of erector spinae plane block in lumbar spine surgery: A systematic review and meta-analysis - Oh, Seok Kyeong; Lim, Byung Gun; Won, Young Ju; Lee, Dong Kyu; Kim, Seong Shin (Journal of clinical anesthesia, 2022)
Erector spinae plane block (ESPB) has gained popularity for perioperative analgesia in various surgeries. However, its efficacy in lumbar surgery remains unclear. This review aimed to determine whether ESPB could improve analgesic efficacy in lumbar spine surgery. A meta-analysis of randomized controlled trials. Perioperative setting. Patients undergoing lumbar spine surgery under general anesthesia. We searched the databases including PubMed, Cochrane Library, EMBASE, Web of Science etc. for published eligible controlled trials comparing ESPB with control (no block/sham block) in lumbar spine surgery. The primary outcome was opioid consumption in the first 24 h after surgery. Twelve studies comprising 665 participants were included. Compared to the control, ESPB reduced the opioid (morphine milligram equivalents) consumption significantly 24 h after surgery [mean difference (MD) = −14.55; 95% confidence interval (CI), −21.03 to −8.07; P < 0.0001] and lowered the pain scores at various time points (at rest or during movement) for 48 h after surgery. ESPB increased the patient satisfaction score (0−10) (MD = 2.38; 95% CI, 2.10 to 2.66; P < 0.0001), decreased the postoperative nausea and vomiting [risk ratio (RR) = 0.36; 95% CI, 0.20 to 0.67; P = 0.001], and minimized the length of hospital stay (MD = −1.24 days; 95% CI, −2.31 to −0.18; P = 0.02). Furthermore, subgroup analysis revealed additional reduction in opioid consumption by the block approach at the vertebral level of incision/operation than that at the fixed thoracic/lumbar level. However, considerable heterogeneity and low-grade quality of evidence were observed. ESPB provided effective postoperative analgesia resulting in better patient satisfaction and recovery with decreased postoperative nausea and vomiting in patients undergoing lumbar surgery compared to the control. However, the low-grade quality of evidence compromised the findings, therefore further high-quality of evidence is required. PROSPERO registration number: CRD42021233362. •Evidence for ESPB use in lumbar spine surgery is insufficient.•We performed evidence synthesis of 12 RCTs on ESPB vs. control for lumbar surgery.•ESPB improved analgesic efficacy by reducing opioid consumption 24 h after surgery.•ESPB increased patient satisfaction and decreased postoperative nausea and vomiting.•ESPB at the incision/operation level reduced opioid use more than at the fixed level.